Psychological aspects of coping and adjustment of infertility and role of psychologist - MN Farahani (JRI, 2001)
An extensive review of infertility literature investigation has shown that, psychological factors have little role in causing infertility, but it has not been rejected that stress has effect on spermatogenesis and ovulation. Though psychological factors are not major factors in infertility, but there has been emphasis that infertility can cause negative psychological effects on psychological health of person. The goal of this study is determination of the role of major factors in coping and adjustment toward infertility and also determination of the role of psychologist. In this study, psychological and behavioral factors were evaluated and way of control, coping strategies toward it and social supports has been pointed out. In this study it is being shown that, change in thought will bring about the change in action. In this regard, psychologist by having treatment knowledge leads the thoughts of infertile person toward accepting the reality of infertility and when medical sciences are not able to change the present fertility condition, psychologist will help them to accept the reality of their being infertile and cope with it. Also, extensive social support, has important role in decreasing of the stress resulted from infertility.
Keywords: Infertility, Psychological factors, Coping, Psychologist, Child care